HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN KUALITAS TIDUR PADA REMAJA JEMAAT GMIM IMANUEL LEILEM RAYON BETLEHEM - Laada, Yohana (Journal Of Community & Emergency, 2024)
Social media is a medium that is not foreign to the public, including teenagers. Teenagers’ habit of using social media while on the move even at night before going to bed can disrupt their sleep patterns so that their sleep quality becomes poor. The purpose of this study was to determine the relationship between the use of social media and sleep quality in the teens of GMIM Imanuel Leilem Rayon Bethlehem. The type of research used in this research is quantitative. The research design that will be used is descriptive analytic research design with a sectional cross approach. Population in this study is the teens of the GMIM Imanuel Leilem Rayon Bethlehem congregation with a total of 34 respondents. Data were analyzed using chi-square test with 95% significance =0.05. Based on the results of statistical tests using the chi-square test, the p-value = 0.000 is smaller than the value of = 0.05. It means that Ho is rejected, then there is a relationship between the use of social media and sleep quality in the teens of the GMIM Imanuel Leilem Rayon Bethlehem. The conclusion of this study is that the teens of the GMIM Imanuel Leilem Rayon Bethlehem congregation are active in the use of social media and sleep quality is categorized as poor. There is a relationship between the use of social media with sleep quality in the teens of the GMIM Imanuel Leilem Rayon Bethlehem Congregation.